Analisis Pengelolaan Limbah Medis Padat untuk Mewujudkan Konsep Green Hospital di RSUP Dr. M. Djamil Padang - Herman, Pratiwi; Nopriadi, Nopriadi (Universitas Riau, 2020)
A hospital can apply Green Hospital concept in order to reduce even hospital environment and global environment pollution. The amount of patients at Dr. M. Djamil Padang hospital is 250.000-350.000 every year which make hospital generates medical waste ±400 kg/day on giving health service. Therefore, Dr. M. Djamil Padang hospital should have integrated and sustainable solid medical waste management. Purpose of this research is to analyze the management of solid medical waste management at Dr. M. Djamil Hospital on creating Green Hospital concept. Study of this research is qualitative study. This research was conducted on March-June 2018. There are 9 informants which determined by purposive sampling technique. Data is collected with in-depth interview, observation, and document reviewing. Data are analyzed by data reduction, presentation of data, and conclusion. Data validity were used source triangulation and method triangulation. Input component: hospital has writtern procedure in solid medical waste management, cost and staff regarding solid medical waste management is sufficient, all facilities is appropriate except for temporary storage for medical waste. Process component: waste segregation is carried out according to its character. Waste transportation to temporary storage uses trolly, howeverit doesn’t use special lane. Hospital cooperates with third party on exterminating medical waste with incinerator. Output component: overall, implementation of solid medical waste management at Dr. M. Djamil Hospital Padang has been in accordance with the Indonesian health regulation No. 1204/2004 and hospital has conducted the efforts towards green hospital by doing appropriate solid medical waste management. Referenced to the Indonesian health regulation No. 1204/2004, solid medical waste management at Dr. M. Djamil hospital is carried out properly. But there are still problems found, such as temporary storage is not in accordance with the standard. To achieve Green Hospital, hospital can fix broken facilities and apply waste reduction program.